Exploring the validity of perceived velocity in lower-limb resistance exercises with a cluster-set configuration - Luis Mario Gómez-Miranda; José E. Bimbela; Ángel Rodríguez-Chávez; Rodrigo Merlo; Luis H. Palma; Diego A. Bonilla (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This feasibility study aimed to explore the relationship between mean propulsive velocity (MPV) and a scale of perceived velocity (SPV) in back-squat and deadlift exercises performed with heavy loads during a cluster-sets resistance training (CS-RT). Twelve resistance trained males (24.1[2.94] years; 80.7[9.05] kg; 172[4.7] cm; 19.1[6.17] %BF; 4.71[2.72] years of training experience) participated. Participants visited the laboratory three times, spaced 72 to 96 hours. Load-velocity profiles for each exercise were measured in first visit. During the second and third visits, participants engaged in CS-RT sessions with different intra-set rest period (20 vs 40 seconds, randomly), and consisted of three sets of squat and deadlift exercises at 80%1-RM. Each set concluded upon reaching a 10% velocity loss on two occasions. Bayesian Pearson correlation coefficients (r), 95% credible intervals (95%CrI) and Bayes factors (BF10) were computed to assess the relationship between variables. A low positive correlation was observed between MPV and SPV in deadlift (r=0.368, 95%CrI [0.144, 0.544]), with strong evidence supporting the alternative hypothesis (BF10=20.7). Interestingly, moderate correlation values were observed in the 40-second CS-RT configuration (r=0.47, 95%CrI [0.144, 0.544]) and in the first set of the deadlift (r=0.44, 95%CrI [0.118, 0.654]). Conversely, a negligible Bayesian correlation was identified for squat (r=0.101, 95%CrI [-0.132, 0.319]), with substantial evidence favoring the null hypothesis (BF10=0.208). In conclusion, a positive correlation between MPV and SPV in deadlift during a CS-RT configuration, indicating potential utility for perceived velocity. However, velocity feedback prior SPV use and validity for squatting warrants further investigation.